2020
DOI: 10.1523/eneuro.0081-19.2020
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoid Signaling Recruits Astrocytes to Modulate Presynaptic Function in the Suprachiasmatic Nucleus

Abstract: Significance Statement Astrocytes are a critical component of the neural network in the suprachiasmatic nucleus (SCN) required for the generation of precise circadian rhythms. We hypothesized that postsynaptic SCN neurons recruit astrocytes via endocannabinoid signaling to modulate presynaptic GABA release. We demonstrate, using a combination of approaches including whole-cell patch-clamp electrophysiology, GCaMP6 calcium imaging in astrocytes, pharmacology, and manipulation of intracellular signaling cascades… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 62 publications
0
26
0
Order By: Relevance
“…Interestingly, astrocytes accumulate high levels of calcium during wake cycles in order to encode sleep need [209][210][211], similar to astrocytic calcium encoding futility-induced passivity in zebrafish [178]; enhancing astrocytic calcium caused perpetual sleep in Drosophila [210] and reducing astrocytic calcium is necessary for slow-wave sleep in mouse [207]. Finally, this transition in behavioral state is dependent on the local concentration of neurotransmitters (dopamine, serotonin, and endocannabinoids) sensed by astrocytic receptors [212,213]. It will be interesting to test whether high levels of neuronal activity during the day also drive sleep recovery (e.g.…”
Section: Astrocytes and Circuit Pattern Generationmentioning
confidence: 99%
“…Interestingly, astrocytes accumulate high levels of calcium during wake cycles in order to encode sleep need [209][210][211], similar to astrocytic calcium encoding futility-induced passivity in zebrafish [178]; enhancing astrocytic calcium caused perpetual sleep in Drosophila [210] and reducing astrocytic calcium is necessary for slow-wave sleep in mouse [207]. Finally, this transition in behavioral state is dependent on the local concentration of neurotransmitters (dopamine, serotonin, and endocannabinoids) sensed by astrocytic receptors [212,213]. It will be interesting to test whether high levels of neuronal activity during the day also drive sleep recovery (e.g.…”
Section: Astrocytes and Circuit Pattern Generationmentioning
confidence: 99%
“…These mechanisms should also be considered in exploring the range of receptor actions that could be involved in affecting sleep. For example, a recent study found that neurons in the suprachiasmatic nucleus, a hypothalamic region critical for controlling the circadian rhythm, release eCBs that activate intracellular astrocyte signaling which subsequently influences circadian clock timing (Hablitz et al, 2020 ).…”
Section: Molecular Mechanisms Potentially Underlying Cannabinoid Effementioning
confidence: 99%
“…However, FURA-2 does not allow for the long-term measurement of Ca 2+ oscillations because it is eventually cleared from the cytoplasm. In contrast to these results, studies that have expressed genetically encoded Ca 2+ sensors such as GCaMP or Cameleon in the SCN have shown that Ca 2+ rhythms are only partially reduced in the absence of neuronal firing, suggesting that intracellular signaling and possibly also non-action potential dependent signaling (e.g., Hablitz et al, 2020 ) also plays a role in regulating the oscillations of [Ca 2+ ] i ( Enoki et al, 2012 ; Noguchi et al, 2017 ). Intracellular pathways could be associated with TTFLs of clock genes.…”
Section: Ca 2+ Rhythms In Biological Clocks Are Regulated By Intracellular and Extracellular Signalsmentioning
confidence: 71%